2005
DOI: 10.1007/s00125-005-1810-7
|View full text |Cite
|
Sign up to set email alerts
|

Degradation products of proteins damaged by glycation, oxidation and nitration in clinical type 1 diabetes

Abstract: Aims/hypothesis: Hyperglycaemia in diabetes is associated with increased glycation, oxidative stress and nitrosative stress. Proteins modified consequently contain glycation, oxidation and nitration adduct residues, and undergo cellular proteolysis with release of corresponding free adducts. These free adducts leak into blood plasma for eventual renal excretion. The aim of this study was to perform a comprehensive quantitative analysis of protein glycation, oxidation and nitration adduct residues in plasma pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
211
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(233 citation statements)
references
References 55 publications
10
211
1
3
Order By: Relevance
“…However we did not observe increase in free iron in group II cases who were in good glycemic control (The means of the parameters in all the groups are presented in Table I). According to previous studies, poor glycemic control leads to increase in the levels of lipid hydroperoxides and decrease in total thiols (15). In line with previous studies we found significant decrease in protein bound thiols (p<0.01), which may be due to increased oxidative degradation of proteins especially albumin or increased consumption of this antioxidant in stress environment.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However we did not observe increase in free iron in group II cases who were in good glycemic control (The means of the parameters in all the groups are presented in Table I). According to previous studies, poor glycemic control leads to increase in the levels of lipid hydroperoxides and decrease in total thiols (15). In line with previous studies we found significant decrease in protein bound thiols (p<0.01), which may be due to increased oxidative degradation of proteins especially albumin or increased consumption of this antioxidant in stress environment.…”
Section: Resultssupporting
confidence: 91%
“…Existence of oxidative stress in diabetes is well proved by numerous studies (14). Previous studies have proved that poor glycemic control causes glycation of proteins and increased oxidative damage of proteins which are responsible for the diabetes related complications (15). In this context, the presence of oxidative stress, hyperglycemia, hyperinsulinaemia, iron overload, and protein glycation will all lead to insulin resistance and poor glycemic control that causes early appearance of complications associated with diabetes (3).…”
Section: Introductionmentioning
confidence: 99%
“…The hydroimidazolones MG-H1 and 3DG-H emerged as sensitive indicators of this because the concentrations of their precursors increase rapidly (21) in response to increased glucose concentration. Hydroimidazolones are also the major quantitative glycation adducts formed from these precursors, with diabetes-associated MG-H1-free adduct concentrations achieving levels 3-to 10-fold higher than other free AGE adducts, as shown in the present and prior studies (26,39). CML probably emerged as an indicator sensitive to PPG because oxidative stress enhanced in the postprandial period increased the rate of degradation of fructosyl-lysine to CML.…”
Section: Correlations Between Indicators Of Glycemic Control and Plassupporting
confidence: 71%
“…Sera from patients with type 1 diabetes mellitus bind these complexes much more strongly than they bind the glutamic acid decarboxylase monomer. Thus, oxidative modification of glutamic acid decarboxylase may be important in type 1 diabetes mellitus patients pathogenesis [6,39].…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%